Lung Ultrasound Findings Detected During Inpatient Echocardiography Are Common and Associated With Short‐ and Long‐term Mortality. (20th December 2017) - Garibyan, Vartan N.; Amundson, Stanley A.; Shaw, David J.; Phan, James N.; Showalter, Brian K.; Kimura, Bruce J.
Abstract : Objectives: Although pulmonary abnormalities are easily seen with standard echocardiography or pocket‐sized ultrasound devices, we sought to observe the prevalence of lung ultrasound apical B‐lines and pleural effusions and their associations with inpatient, 1‐year, and 5‐year mortality when found in hospitalized patients referred for echocardiography. Methods: We reviewed 486 initial echocardiograms obtained from consecutive inpatients over a 3‐month period, in which each examination included 4 supplemental images of the apex and the base of both lungs. Kaplan‐Meier survival curves were used to compare mortality rates among patients with versus without lung findings. Cox proportional hazard regression was used to determine the relative contributions of age, sex, effusions, and B‐lines to overall mortality. Results: Of the 486 studies, the mean patient age ± SD was 68 ± 17 years; the median age was 70 years (interquartile range, 27 years); and 191 (39%) had abnormal lung findings. The presence versus absence of abnormal lung findings was related to initial‐hospital (8.9% versus 2.0%; P  = .001), 1‐year (33% versus 14%; P  < .001), and 5‐year (56% versus 31%; P  < .001) mortality. Ultrasound apical B‐lines and pleural effusions were both independently associated with increased mortality during initial hospitalization (hazard ratio [HR], 4.3; 95% confidence interval [CI], 1.7–11.0; and HR, 2.5; 95% CI, 1.1–6.0, respectively). Pleural effusions were also associated with increased 1‐year mortality (HR, 2.3; 95% CI, 1.5–3.4). Conclusions: In hospitalized patients undergoing echocardiography, the simple addition of 4 quick 2‐dimensional pulmonary views to the echocardiogram often detects abnormal findings that have important implications for short‐ and long‐term mortality.